Hand Osteomyelitis: Exploratory Associations of Admission C-Reactive Protein and MRI with Surgical Burden and Hospital Length of Stay - Jessica Köller; Alberto Alfieri Zellner; Jonas Roos; Johanna Thiele; Lisa Fiona Roder; Mari Babasiz; Kristian Welle; Christian Prangenberg (Journal of Clinical Medicine, 2026)
Background: Hand osteomyelitis is an uncommon but potentially devastating infection associated with prolonged treatment, repeated surgical interventions, and risk of amputation. Owing to its rarity, evidence regarding prognostic factors and optimal management remains limited. This study aimed to evaluate the clinical characteristics, microbiological findings, treatment strategies, and outcomes of patients with hand osteomyelitis, with particular emphasis on the association of admission inflammatory markers, immunosuppression, and preoperative magnetic resonance imaging (MRI). Methods: A retrospective single-center cohort study was performed over a 11-year period at a tertiary referral hospital. Patients with clinically and/or histopathologically confirmed hand osteomyelitis were identified using ICD-10-GM codes. Demographic characteristics, etiology, microbiological and histopathological findings, laboratory parameters, imaging, surgical treatment, antibiotic therapy, and length of hospital stay were reviewed. Correlations between admission C-reactive protein (CRP), leukocyte count, number of surgical procedures, and hospital stay were analyzed using Pearson’s correlation coefficient. Results: Fourteen patients were included (mean age, 53.7 years; 64.3% female). Osteomyelitis predominantly affected the distal phalanx (92.9%). Immunosuppression or immunocompromising comorbidities were present in 64.3% of patients. Staphylococcus aureus, methicillin-resistant Staphylococcus aureus, and Streptococcus pyogenes were the most frequently isolated pathogens, while immunosuppressed patients exhibited more polymicrobial infections. The mean admission CRP was 87.8 mg/L and was markedly higher in immunosuppressed than in non-immunosuppressed patients (128.5 vs. 14.6 mg/L). Amputation was required in 78.6% of patients, with a mean of 3.3 surgical procedures per patient. Admission CRP is associated with both length of hospital stay (r = 0.61) and number of surgical procedures (r = 0.73), whereas leukocyte count showed only weak correlations. Patients who underwent MRI had a shorter mean hospital stay than those without MRI (13.4 vs. 19.6 days). The mean duration of antibiotic therapy was 29.3 days. Conclusions: In this small cohort, admission CRP showed a potential association with disease severity in hand osteomyelitis, with higher levels observed in patients requiring more extensive surgical treatment and longer hospitalization. MRI was associated with a shorter hospital stay, suggesting a possible role of early advanced imaging in facilitating timely diagnosis and treatment planning. Immunosuppressed patients tended to exhibit higher inflammatory markers and more frequently polymicrobial infections, although these findings should be interpreted cautiously given the limited sample size. Overall, these observations are exploratory and require confirmation in larger, preferably prospective studies.